The Effect of Thiamine Supplementation for Critically Septic Patient: An Evidence-Based Case Report - Ayu Diandra Sari; Melyarna Putri; Sheena R. Angelia; Mulianah Daya; Anak Agung Eka Widya Saraswati; Diyah Eka Andayani; Diana Sunardi (World Nutrition Journal, 2021)
Sepsis has been accounted for various burdens worldwide, especially in critically ill patients. This could eventually lead to inflammatory response, provocation ischemia and lactic acidosis. On the other hand, thiamine was suggested as a coenzyme which could improve the outcome of those patients. Thus, we conducted an evidence-based case study with research on PubMed, ProQuest, and Scopus using a search strategy focusing on RCT or cohort study on thiamine supplementation/level towards the outcome of critically ill patients with sepsis. We found three articles eligible for review after full-text assessment. Articles were appraised using the University of Oxford’s tools for critical appraisal. It was known that all studies were good in terms of validity and applicability. This study showed that thiamine supplementation could improve lactate clearance and reduce mortality risk, moreover, thiamine deficiency could increase the risk of lactate acidosis. However, a high level of thiamine was associated with a high level of lactate in patients with liver failure. Therefore, thiamine supplementation could be recommended for critically ill patients with sepsis and normal liver function. Further research, such as RCT or systematic review on thiamine supplementation for age groups to make this study more applicable.